Improving Expressive Language of Children Aged 5–6 Years Through Role-Play Method at Tk Insan Cendikia Legok - Fitria, Evy; Novianti, Tri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Early Childhood Education (ECE) is a crucial stage for developing expressive language, which is strongly influenced by stimulation and the learning environment. This study aimed to enhance the expressive language skills of children aged 5–6 years at TK Insan Cendikia–Legok through the role-play method. The research employed Classroom Action Research (CAR) using the Kemmis & Taggart spiral model consisting of planning, action, observation, and reflection over three cycles. Each cycle included three meetings with themes such as doctor, market vendor, and fruit and vegetable seller. Data were collected through participatory observation, semi-structured interviews, documentation, and field notes, then analyzed using descriptive percentages and qualitative verification. The results indicated significant improvement: from only 2 children developing as expected initially, to 3 in cycle I (50.39%), 6 in cycle II (67.18%), and 8 in cycle III (79.29%). Role-play proved effective in fostering vocabulary, sentence structure, intonation, expression, and social interaction, while also boosting confidence, imagination, and social skills.